2003
DOI: 10.1046/j.1420-9101.2003.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between ultraviolet coloration, overwinter survival and offspring sex ratio in the blue tit

Abstract: We studied the correlations between offspring sex ratio, UV coloration and overwinter survival in a population of blue tits, breeding in Gotland, Sweden, over three consecutive breeding seasons. In 2 of 3 years, we found that females paired to males with relatively brighter UV-coloration produced a greater proportion of sons in their broods, and that this effect was significant with all 3 years combined, despite a significant year by male UV interaction. In addition, we found other correlates of sex ratio (bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
4
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 57 publications
7
121
4
2
Order By: Relevance
“…Recent research concluded that avian plumage signals can exploit intertaxon perceptual differences (36), and inclusion of conspecific signals hidden from human investigators but shown in this study to be available to birds could further facilitate understanding of functions of plumage coloration. For example, since the discovery of sexual differences in the blue-UV crown coloration of blue tits (11)(12), color in this feather patch has been shown to be important in social interactions (37), mate choice (38), parental care (39), and offspring sex ratios (40).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research concluded that avian plumage signals can exploit intertaxon perceptual differences (36), and inclusion of conspecific signals hidden from human investigators but shown in this study to be available to birds could further facilitate understanding of functions of plumage coloration. For example, since the discovery of sexual differences in the blue-UV crown coloration of blue tits (11)(12), color in this feather patch has been shown to be important in social interactions (37), mate choice (38), parental care (39), and offspring sex ratios (40).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies, however, have reported mixed (Radford & Blakey, 2000;Griffith et al, 2003;Korsten et al, 2006) or negative results (Grindstaff et al, 2001;Leech et al, 2001;Rosivall et al, 2004;Ferree, 2007). Most of these previous studies have concentrated on the physical traits of males, and behavioral sexual traits such as courtship songs have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The UV reflectance may also function as a signal in malemale territorial conflicts during the breeding season, as breeding males were shown to react more aggressively towards a mounted conspecific male with natural crown UV reflectance than towards a mount with reduced crown UV reflectance (Alonso-Alvarez et al 2004; but see Korsten et al 2007). Possibly, blue tit crown UV reflectance signals individual viability or quality, as in a Swedish population, males with higher UV reflectance during the breeding season were found to have higher subsequent over-winter survival (Sheldon et al 1999;Griffith et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During winter, blue tits (and some other species of the Paridae family) aggregate in loosely organized foraging flocks ('basic flocks') that roam the area in search for food (Colquhoun 1942;Ekman 1989). We suggest that, within these flocks, highly UV-reflective individuals may be more successful at monopolizing food sources, which could be a proximate explanation for their demonstrated greater survival chances (Sheldon et al 1999;Griffith et al 2003). To evaluate if highly UV-reflective individuals have higher dominance and priority access to food sources, we related the dominance of individuals at an artificial food source to spectrophotometric measurements of their crown plumage.…”
Section: Introductionmentioning
confidence: 99%